Refractive Shifts and Changes in Corneal Curvature Associated With Antibody–Drug Conjugates. Issue 6 (23rd June 2022) - Canestraro, Julia; Hultcrantz, Malin; Modi, Shanu; Hamlin, Paul A.; Shoushtari, Alexander N.; Konner, Jason A.; Tew, William P.; Iyengar, Neil M.; Heinemann, Murk; Abramson, David H.; Francis, Jasmine H.
Abstract : Purpose: Antibody–drug conjugates (ADCs) are a class of cancer drug wherein some are associated with corneal abnormalities, but there is a dearth of published information on refractive shifts in patients receiving ADCs. Here, we evaluated the dynamics of refractive error and keratometry readings in patients with ADC-related keratopathy and microcyst-like epithelial changes (MECs). Methods: This study is a retrospective case series including 58 eyes of 29 patients with ADC-related keratopathy from a single tertiary care cancer referral center (MSKCC). One eye (29 total) was randomly assigned for statistical analysis. In addition, a subset analysis of MEC location–refractive error correlation was performed on 20 eyes. Clinical records including slitlamp examination, indirect ophthalmoscopy, calculated spherical equivalence (SE), keratometry, and visual acuity were recorded at baseline, during, and off treatment. Results: A subset analysis of MEC location–refractive error correlation of 20 eyes revealed the following: Peripheral MECs were significantly associated with hyperopic shifts ( P value < 0.001) and paracentral/central associated with myopic shifts ( P value < 0.001). In the full cohort and on drug, the greatest change in SE from baseline was myopic (68%, as high as −4.75 D) and hyperopic (32%, as much as +3.75 D). Eighty-nine percent had a change in vision from baseline while on drug, but at the 3-month follow-up off drug, SE and vision returned to baseline in 33% and 82% of eyes. Conclusions: Peripheral MECs were significantly associated with hyperopic shifts, and paracentral/central MECs were associated with myopic shifts. While on drug, most eyes had a myopic refractive shift, which corresponded with corneal steepening.